Anatomical structure of the reed flower Echinacea purpurea (L.) Moench - Mamykova, R.U.; Jamalova, G.T.; Bitemirova А.Е.; Akinbekova, Zh.V.; Orynbay, Zh.E. (Fundamental and Experimental Biology, 2022)
The article presents the results of scientific research on the determination of the anatomical structure of the reed flower Echinacea purpurea(L.) Moench introduced in South Kazakhstan. To prepare the micropreparation, the lingual flowers of the plant were taken; they are purple, 2.5–6 cm long, inner 4mm long. The films of the flower are lanceolate awl-shaped, 1–1.5 cm long, 1–1.5 mm wide, with a straight prickly tip. Previously, the anatomical structure of the leaf, stem and root of Echinacea purpurea were studied. The purpose of the study is to examine theanatomical structure of the lingual flower of E. Purpurea to identify diagnostic signs characteristic of thistype, necessary for the development of effective and low-toxic domestic drugs. Information about the anatomical features of the generative organs of the studied species is given for a complete diagnosis of medicinal plant raw materials, which can be seen in microphotographs taken by a computer microphotometer. The following anatomical features necessary for the identification of raw materials have been identified, i.e., signs by which the studied object can be distinguished from similar parts of another plant: the outline of epidermal cells on the adaxial structure is rectilinear, the projection is polygonal, on the abaxial — weakly branched; stomata are not submerged, anomocytic type; the structure of the mesophyll of the lingual flower is aerenchyma with well-defined intercellular lacunae; the presence of lamellar collenchyma under the abaxial epidermis; conducting bundles are closed collateral; the location of schizogenic secretory receptacles above conducting bundles.